Advocating for Excellence: Legal Strategies in Shaping Higher Education as a World-Class Research and Education Hub (Case of Indonesia, Oman, and United Arab Emirates) - Riyanto, R Benny; Fibrianti, Nurul; Irawaty, Irawaty; Ezzerouali, Souad Ahmed; Sarhan, Adnan Ibrahim (Universitas Negeri Semarang, 2025)
This paper explores the role of legal strategies and advocacy in shaping higher education institutions into world-class research and education hubs, with a comparative focus on Universitas Negeri Semarang (UNNES) in Indonesia, Dhofar University in Oman, and the University of Sharjah in the United Arab Emirates. Central to this analysis is the development of Centers of Excellence (CoEs) as catalysts for academic innovation, international collaboration, and institutional prestige. The study investigates how legal frameworks—ranging from national laws to internal university policies—facilitate or hinder the strategic growth of CoEs in each context. It highlights how legal advocacy can drive policy reform, secure essential resources, safeguard intellectual property, and promote academic freedom and international accreditation. By examining case studies from the three institutions, the paper underscores the importance of legal professionals not only as compliance officers but as key actors in institutional transformation. Ultimately, the research demonstrates that a robust, forward-thinking legal strategy is essential to advancing the global aspirations of universities in emerging knowledge economies.